2017
DOI: 10.3892/mmr.2017.7975
|View full text |Cite
|
Sign up to set email alerts
|

DJ‑1 alleviates high glucose‑induced endothelial cells injury via PI3K/Akt‑eNOS signaling pathway

Abstract: Hyperglycemia mediated endothelial cells (ECs) injury is closely associated with diabetic vascular complications. It was revealed that DJ‑1 possesses cellular protective effects by suppressing oxidative stress. The present study aimed to investigate the beneficial effects of DJ‑1 on high glucose (HG)‑induced human umbilical vein endothelial cell (HUVEC) injury and to elucidate its underlying mechanisms. HUVECs were incubated under 5.5 mM (control group) or 25 mM D‑glucose (HG group) and then transfected with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…BAX localizes largely in the cytoplasm, redistributes to the mitochondria in response to stimuli, triggers the release of cytochrome c, and consequently induces mitochondrial dysfunction (55). It has been reported that LY294002 treatment inhibits the PI3K/Akt pathway, suppresses BAX translocation to the mitochondria and reduces the release of mitochondrial ROS (56). The knockdown of DHODH has been shown to increase BAX expression (57).…”
Section: Discussionmentioning
confidence: 99%
“…BAX localizes largely in the cytoplasm, redistributes to the mitochondria in response to stimuli, triggers the release of cytochrome c, and consequently induces mitochondrial dysfunction (55). It has been reported that LY294002 treatment inhibits the PI3K/Akt pathway, suppresses BAX translocation to the mitochondria and reduces the release of mitochondrial ROS (56). The knockdown of DHODH has been shown to increase BAX expression (57).…”
Section: Discussionmentioning
confidence: 99%
“…The major finding of our studies is that nitrosative stress is a novel mechanism of poor coronary collateral circulation in patients following acute MI. Current treatments of acute MI have focused on increasing NO bioavailability to induce coronary arterial relaxation (Munzel and Gori, 2013 ; Tian et al, 2018 ). However, continuous exposure to nitrate esters can lead to nitrate tolerance, causing the loss of vascular responsiveness to nitrates (Bai et al, 2018 ; Zhou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a molecular disorder of reactive oxygen metabolism and plays a key role in the pathogenesis of endothelial dysfunction and atherosclerosis [ 45 , 46 ]. NADPH oxidase catalyzes the generation of ROS.…”
Section: Discussionmentioning
confidence: 99%